Position estimation using the Digital Audio Broadcast (DAB) signal - Palmer, Duncan. (2011)
Over the past decades, there have been a number of trends that have driven the desire to improve the ability to navigate in all environments. While the Global Positioning System has been the driving factor behind most of these trends, there are limitations to this system that have become more evident over time as the world has increasingly come to rely on navigation. These limitations are mostly due to the low transmission power of the satellites, where navigation signals broadcast from space are comparatively weak, especially by the time they have travelled to receivers on the ground. This makes the signals particularly vulnerable to fading in difficult environments such as "urban jungles" and other built up areas. The low signal-to-noise ratio (SNR) also means, that the signals are susceptible to jamming, both hostile and accidental.